Pervasive role of the long noncoding RNA DNM3OS in development and diseases. (1st May 2022) - Fellah, Sandy; Larrue, Romain; Truchi, Marin; Vassaux, Georges; Mari, Bernard; Cauffiez, Christelle; Pottier, Nicolas
Abstract: Thousands of unique noncoding RNAs (ncRNAs) are expressed in human cells, some are tissue or cell type specific whereas others are considered as house‐keeping molecules. Studies over the last decade have modified our perception of ncRNAs from transcriptional noise to functional regulatory transcripts that influence a variety of molecular processes such as chromatin remodeling, transcription, post‐transcriptional modifications, or signal transduction. Consequently, aberrant expression of many ncRNAs plays a causative role in the initiation and progression of various diseases. Since the identification of its developmental role, the long ncRNA DNM3OS (Dynamin 3 Opposite Strand) has attracted attention of researchers in distinct fields including oncology, fibroproliferative diseases, or bone disorders. Mechanistic studies have in particular revealed the multifaceted nature of DNM3OS and its important pathogenic role in several human disorders. In this review, we summarize the current knowledge of DNM3OS functions in diseases, with an emphasis on its potential as a novel therapeutic target. This article is categorized under: RNA in Disease and Development > RNA in Disease RNA in Disease and Development > RNA in Development Abstract : Overview of the multifunctional roles of DNM3OS.